2005
DOI: 10.1103/physrevb.72.165423
|View full text |Cite
|
Sign up to set email alerts
|

Structure and formation energy of carbon nanotube caps

Abstract: We present a detailed study of the geometry, structure and energetics of carbon nanotube caps. We show that the structure of a cap uniquely determines the chirality of the nanotube that can be attached to it. The structure of the cap is specified in a geometrical way by defining the position of six pentagons on a hexagonal lattice. Moving one (or more) pentagons systematically creates caps for other nanotube chiralities. For the example of the (10,0) tube we study the formation energy of different nanotube cap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
119
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(121 citation statements)
references
References 33 publications
1
119
0
Order By: Relevance
“…Following the two rules in §5a, the two modes of adding bars in figure 5a can be implemented. Such graphene-like planar structure can be rolled up into tensegrity structures having the shape of a capped carbon nanotube (Reich et al 2005), as shown in figure 6b.…”
Section: (B) Examplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the two rules in §5a, the two modes of adding bars in figure 5a can be implemented. Such graphene-like planar structure can be rolled up into tensegrity structures having the shape of a capped carbon nanotube (Reich et al 2005), as shown in figure 6b.…”
Section: (B) Examplesmentioning
confidence: 99%
“…According to the definition of tensegrity (Pugh 1976), the structure shall have no node shared by two bars. Therefore, it is convenient to set the connectivity matrix of the bars as…”
Section: Direct Enumeration Schemementioning
confidence: 99%
See 1 more Smart Citation
“…24,25 In order to study the stability of BiOCl with different layers, theformation energies of bulk, 6-layer, 4-layer, 3-layer, bilayer, and monolayer are calculated. It can be expressed as 26,27 = − − − where is the formation energy of crystals, represent the total energy …”
Section: Crystal Structure and Formation Energy Of Biocl With Differementioning
confidence: 99%
“…Growth into the capped tubular structure of the SWNT then ensues. The (n,m) chirality is often assumed to be decided at the stage of cap formation [25,26]. Although the VLS model reasonably explains the phase separation dynamics between carbon and iron, it is still controversial whether SWNT growth always requires the formation of metal carbide or not.…”
Section: Introductionmentioning
confidence: 99%